PRE-SERVICE TEACHERS’ ATTITUDES TOWARD INCLUSIVE EDUCATION: IMPACT OF EXPOSURE TOINCLUSIVE EDUCATION (Proceedings of International Conference on Special Education, 2025)
This qualitative study examined how field-based experiences influence pre-service teachers’ attitudes and preparedness for inclusive education. Conducted with 321 pre-service teachers at a Philippine teacher education institution, the research explored how exposure to inclusive teaching strategies, direct classroom engagement, and limited access to assistive technologies shaped their professional growth. Thematic analysis revealed a clear progression from initial uncertainty and limited understanding to increased confidence, empathy, and commitment to inclusive practice. Key themes included transformative learning experiences, post-exposure attitudinal shifts, development of inclusive teaching strategies, and professional growth. While field experience and reflective practice proved central to attitudinal change, participants also identified a lack of preparation in using assistive technologies. These findings support the value of experiential learning in teacher education and highlight the need to integrate inclusive technologies into pre-service training. The study recommends embedding structured fieldwork, reflective practice, mentorship, and assistive technology modules in teacher preparation programs to promote inclusive competence.